Reaksi Pasar Modal di Sektor Consumer Non Cyclical Sebelum dan Sesudah Diumumkan Pandemi Covid-19 - Prasetyo, David; Murnisari, Retno; Putra, Iwan Setya (Unversitas Islam Madura, 2024)
Consumer non-cyclical companies declined at the beginning of the year due to the COVID-19 pandemic. Contextually, this research is to identify financial statement announcement events on the Indonesia Stock Exchange (IDX) in the non-cyclical consumer sector by conducting a study of informative financial statements to see whether this information affects decisions in stock trading around or outside the observation of financial statements, especially during the COVID-19 pandemic. This type of research is quantitative, using the analysis of expected return, abnormal return, trading volume activity, cumulative abnormal return, cumulative average trading volume activity and parametric and non-parametric methods. The results of this study indicate differences in capital market reactions around and outside the annual financial report issuance period. Furthermore, there are no differences in capital market reactions around and outside the yearly financial report issuance period in 2020, 2021, and 2022 during the COVID-19 pandemic